The Neutral Vowel and the lndeterminate Phoneme (Sprachbund Typology) - Kleiner, Yuri A.; Kaminskaya, Larissa N. (Respectus Philologicus, 2005)
It is erroneous methodologically to identify a set of phonetic features with a unit with a systemic (phonemic) status within a certain language, and even more so, with phonetically similar units (‘sounds’) of different languages. Such a cross-systemic approach to the phoneme is impossible, for the phoneme is a language-specific rather than a universal notion. On the other hand, phonetically similar units in different languages can be the product of linguistically similar contexts (conditions). In this situation, the conditions (contexts) and the units that manifest themselves in these can be regarded as typological characteristics of a group of languages. This applies to the so-called neutral vowel (“schwa”) either (a) limited to phonologically and morphologically weak (phonetically unstressed) positions (non-radical syllables in the Germanic languages) or (b) not characterised by any distributional limitations (the Balkan “schwa”). In the latter case, the phonetically neutral vowel manifests an “indeterminate phoneme”,i. E. the phoneme that can only be defined negatively in terms of (linguistic) distinctive features. Since the contexts in which this phoneme exists are similar in different Balkan languages, and since these contexts may have arisen as a result of contacts of languages where similar processes took place, the indeterminate phoneme (but not the neutral vowel) can indeed be regarded as a Balkanism.
Keywords: Sprachbund typology; language contacts; phonetics and phonology of the Balkan languages; neutral vowel; indeterminate phoneme